ESRA19-0387 Erector spinae plane block as part of an opioid-sparing anaesthetic strategy for breast quadrantectomy and sentinel lymph-node excision: a case-report. (30th August 2019) - Lopes, L; Fernandes, A
Abstract : Background and aims: Breast surgery often requires post-operative opioid analgesia, which has been associated with treatment-resistant chronic pain syndromes, and been suggested as having cancer-spreading potential. Erector spinae plane (ESP) block is a novel approach to thoracic and abdominal pain management which has previously been described as successfully implemented perioperatively in various breast interventions. We hereby present our experience in the management of a quadrantectomy patient. Methods: An otherwise healthy 66-year old woman presented for right-lower quadrantectomy of the right breast with sentinel lymph node excision. An anaesthetic management plan consisting of combined general anaesthesia with right-sided ESP block was devised. Ultrasonography-guided injection of 20cc of 0, 75% ropivacaine along the erector spinae fascial plane at the T5 spinal level was performed preoperatively. General anaesthesia was induced with fentanyl (100mcg) and propofol (120 mg). After supraglottic device placement, maintenance was ensured with sevoflurane. Additional intravenous analgesia was provided with paracetamol (1 g) and ketorolac (30 mg). Results: Haemodynamic stability was noted throughout surgery, with no response to skin incision or tissue dissection. The patient reported no significant pain upon waking or discharge, 24h later. No rescue analgesia was needed during that period and skin numbness representing no significant discomfort subsided over the next day. Conclusions: Our report of a successful implementation of nearly opioid-free anaesthesia in a quadrantectomy patient, by using the novel potential of the ESP-block, suggests that this might be an invaluably safe and effective strategy, not only for pain control, but also as an opioid and anaesthetic-sparing approach, plausibly increasingly useful in debilitated and physiologically fragile patients.